Problems and prospects of trilingual education in Kazakhstan - Karabalina, A.K. (Karagandy University of the name of acad. E.A. Buketov, 2021)
This article discusses the current policy of "Trilingual Education" in the country and its advantages and disadvantages; One of the ways for Kazakhstan to join the ranks of developed countries will be presented, and the harm and benefits of a trilingual education program for the nation will be discussed.
Keywords: Trilingual Education; native language; future and development of the country; foreign language; modern country; international cooperation; language difficulty